Evaluation of FGFR2 gene polymorphism in women with breast cancer - Salehi, Z; Afzali, S; Shabanipour, S; Rahimi, A (Cellular and Molecular Biology, 2015)
Breast cancer (BC) is one of the most frequent cancers among women worldwide. It is a complex polygenic disorder that genetic factors play an important role in disease etiology. The highly significant association of the Fibroblast growth factor receptor 2 (FGFR2) locus with breast cancer risk has been replicated in multiple genome association study; however, it's mechanism of action remains unclear. The aim of this study was to investigate whether the single nucleotide polymorphism (SNP) C-906T within intron 2 of FGFR2 is responsible for susceptibility to breast cancer. This case–control study included 108 breast cancer cases and 108 cancer–free controls. The prevalence of genotype frequencies of the FGFR2 CC/CT/TT was 5.5%, 90.7% and 3.7%, respectively, in cancer cases. Among controls, the distribution of CC, CT and TT genotype was 48.14%, 47.66% and 10.18% respectively. Significant differences in allele and genotype distribution among controls and patients were found (OR, 18.87 95% CI, 7.55-47.16; p = 0.0001). The results from this study suggest that the FGFR2 C-906T polymorphism may be associated to breast cancer in population studied. Well-designed studies with larger sample sizes are needed to confirm the role of FGFR2 SNP in breast cancer risk.